Water-insoluble fibres, threads, and fabrics from lauroyl derivatives of hyaluronan - Horáčková, Lucie; Chmelíčková, Kristýna; Hermannová, Martina; Pitucha, Tomáš; Vágnerová, Hana; Židek, Ondřej; Velebný, Vladimír; Chmelař, Josef (Elsevier Science BV, 2023)
Hyaluronan (HA) is a naturally occurring polysaccharide widely used in medicine and cosmetics. To further broaden its potential, various HA derivatives have been developed with the aim of reducing solubility, slowing degradation, or providing other beneficial properties. However, for most medical applications, these derivatives must be processed into suitable forms. Here we present water-insoluble fibres prepared from lauroyl-modified HA using a wet spinning process. Important properties of the fibres, such as swelling or the degradation rate, can be fine-tuned by adjusting the degree of HA modification. Due to their mechanical properties, the lauroyl HA fibres can be easily processed into threads and subsequently into fabrics of various sizes, shapes, and degrees of porosity. In addition, in vitro cytotoxicity testing of the fibres showed that they were non-cytotoxic. Overall, our results suggest that lauroyl HA fibres are a promising material that could be used to develop a variety of medical devices.
Ve vodě nerozpustná vlákna, nitě a tkaniny z lauroylových derivátů hyaluronanu
Keywords: Lauroyl hyaluronan; Fibre; Wet spinning; Lauroyl hyaluronan; vlákna; mokré spřádání